Molecular Identification of Alternaria Alternata Associated With Leaf Spot Disease in Garlic and Its Eco-Friendly Control Measures - Khatun, Most Shahida; Rayhan, Md Abu; Alam, Nuhu (Journal of Bio-Science, 2024)
Leaf spot disease is considered as one of the devastating disease of garlic that results in significant decrease of crop yield worldwide. The main purpose of this study was to identify the pathogenic fungi of garlic and to find out its eco-friendly control measures. The pathogen (Alternaria alternata) was characterized morphologically and identified through the molecular method. Morphological characters e.g. greyish-black mycelium and unbranched, straight, smooth-walled, and golden brown conidia was identified as the initial indicator. Species level identification was carried out by using sequence analysis of internal transcribed spacer/5.8S ribosomal DNA (rDNA) in which internal transcribed spacer 4 (ITS4) and ITS5 and 5.8S rDNA were amplified by PCR. The results revealed that Potato Dextrose Agar (91 mm) is the best media for the mycelial growth of A. alternata followed by Potato Sucrose Agar and Carrot Agar (55 mm). The best growth was found at 30℃ at pH 6. A. alternata can be controlled biologically with a mix-culture of different species of Trichoderma as T. harzianum, T. reseei, T. asperellum. Culture with two or more species had better inhibitory effects than culture with one species. Lawsonia inermis and Ocimum sanctum extract showed a certain level of significant inhibition against A. alternata, (73.74% and 65.93% respectively). Thus, the present study will be helpful to identify the pathogen of leaf spot disease of garlic and eco-friendly management of the disease in future. J. Bio-Sci. 31(2): 45-53, 2023